2014
DOI: 10.24059/olj.v19i1.494
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Veterans' Success! The Degree Map as an Advising Solution

Abstract: Due to the expected influx of veterans attending college, it is critical that higher education not only be cognizant of the projected growth but also take a proactive stand and properly plan for these students' success. Academic planning begins with advising professionals developing open communications and becoming equipped to guide veteran students through the matriculation process. Veteran students often have difficulty interpreting university scheduling and frequently have access to only a limited advising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…More specifically, research has found that particular competencies stand out as especially valuable for faculty advisors of student veterans, including the ability to read and understand military transcripts (Ryan et al, 2011), facility with the nuances of rules governing the use of military benefits to fund higher education (Ryan et al, 2011), and knowledge about how to apply credits earned in the military to university, divisional, or programmatic graduation requirements rather than simply as free electives (Persky & Oliver, 2010). Moreover, the best faculty advisors focus not just on how to get student veterans graduated, but listen closely to students' individual needs (Ryan et al, 2011;Sportsman & Thomas, 2015) and offer advice for more long-term career development (Richardson, Ruckert, & Marion, 2015;Wilson & Smith, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, research has found that particular competencies stand out as especially valuable for faculty advisors of student veterans, including the ability to read and understand military transcripts (Ryan et al, 2011), facility with the nuances of rules governing the use of military benefits to fund higher education (Ryan et al, 2011), and knowledge about how to apply credits earned in the military to university, divisional, or programmatic graduation requirements rather than simply as free electives (Persky & Oliver, 2010). Moreover, the best faculty advisors focus not just on how to get student veterans graduated, but listen closely to students' individual needs (Ryan et al, 2011;Sportsman & Thomas, 2015) and offer advice for more long-term career development (Richardson, Ruckert, & Marion, 2015;Wilson & Smith, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These cultural differences can mean, for some student veterans at least, difficulty relating to classmates who have comparatively limited life experience, more myopic priorities, and lower levels of maturity (Ryan et al, 2011;Sportsman & Thomas, 2015). Many student veterans also perceive university campuses and faculty in particular to exude an anti-military bias (Anderson & Goodman, 2014;Richardson et al, 2015;Rumann & Hamrick, 2009). To compound these challenges, student veterans returning from deployments may also experience isolation at home, as many returning Pg.…”
Section: Continuedmentioning
confidence: 99%
See 1 more Smart Citation